Formation and Evolution of Multi-Genetic Overpressure and Its Effect on Hydrocarbon Accumulation in the Dabei Area, Kuqa Depression, Tarim Basin, China - Chenxi Wen; Zhenliang Wang (Energies, 2024)
The Kuqa Foreland Basin is an important hydrocarbon-producing basin in western China. The Dabei area is an important zone for hydrocarbon accumulation. High fluid overpressures in the Lower Cretaceous Bashijiqike Formation are related to multi-genetic processes. However, the formation and evolution of pressure remain unclear, hindering the further development of oil and gas migration and accumulation. In this study, the overpressure distribution is described based on a drill stem test and mud density data. The formation and quantification of multi-genetic overpressure were evaluated based on well-logging data and basin simulation technology (Ansys Workbench). The coupling evolution of multi-genetic overpressure was examined based on the basin simulation technique. Finally, the influence of overpressure on hydrocarbon accumulation was explored. The results showed that the residual pressure of the Bashijiqike Formation in the Dabei area ranged from 40 to 60 MPa. The main causes of pressure in the Bashijiqike Formation in the Dabei area were disequilibrium compaction overpressure (2–6 MPa, contribution of 8–15%), tectonic compression overpressure (10 MPa, contribution of 30%), and fracture transfer overpressure (15–20 MPa, contribution of 8–15%). With respect to the evolution process of multiple pressures in the Bashijiqike Formation in the Dabei region, at 0–23.3 Ma, the overpressure due to disequilibrium compaction was <10 MPa and increased slowly to 18 MPa at 2.48–23.3 Ma. At 2.48 Ma, the tectonic compression was enhanced, and the residual pressure reached ~50 MPa. At 1.75–2.48 Ma, fracture activity was enhanced, leading to the generation of fracture transfer overpressure. Under these conditions, the residual pressure exceeded 60 MPa. Finally, the Bashijiqike Formation in the Dabei area is a favorable area for vertical and lateral migration of oil and gas. This study is of great significance to the formation and evolution of multi-origin overpressure in the same basin type and its influence on oil and gas accumulation.